Collective bargaining in developing countries - Carlos Lamarche (IZA World of Labor, 2015)
Because theoretical arguments differ on the economic impact of collective bargaining agreements in developing countries, empirical studies are needed to provide greater clarity. Recent empirical studies for some Latin American countries have examined whether industry- or firm-level collective bargaining is more advantageous for productivity growth. Although differences in labor market institutions and in coverage of collective bargaining agreements limit the generalizability of the findings, studies suggest that work rules may raise productivity when negotiated at the firm level but may sometimes lower productivity when negotiated at the industry level.
Keywords: J5; J24; 330; collective bargaining; developing countries; work practices; labor productivity